2020
DOI: 10.5650/jos.ess19209
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Carotenes and Vitamin E, and Physico-chemical Changes Occurring upon Heating Red Palm Olein Using Deep-fat Fryer, Microwave Oven and Conventional Oven

Abstract: nutritional values of fried products. Indeed, this reaction triggers the formation of harmful new compounds including polymers, free fatty acids and other oxidative substances 6. Cooking oil is commonly used for daily diet preparation. Carotenoid-rich red palm oil is beneficial as it offers vital antioxidants that enhance the well-being of the general population, and fulfil the daily requirement of fatty acids 7. However, a dietary habit survey involving 200 pregnant Nigerian women showed high prevalence of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
0
12
1
Order By: Relevance
“…The primary oxidation products are lipid hydroperoxides. There was a sharp increase in PV from its first reception from 0.12 meq O 2 kg 1 to 2.88 and 3.03 meq O 2 kg 1 for the 26 . The initial low value of PV showed that it was at a low oxidation state before storage.…”
Section: Peroxide Valuementioning
confidence: 90%
“…The primary oxidation products are lipid hydroperoxides. There was a sharp increase in PV from its first reception from 0.12 meq O 2 kg 1 to 2.88 and 3.03 meq O 2 kg 1 for the 26 . The initial low value of PV showed that it was at a low oxidation state before storage.…”
Section: Peroxide Valuementioning
confidence: 90%
“…heating under conventional oven and frying conditions (Loganathan et al, 2020a). A separate study by Loganathan et al (2020b) demonstrated an excellent thermal stability of vitamin E and carotenes exceeding 87% in baked cupcakes made of red palm olein whilst preserving similar sensory characteristics as those containing conventionally refined palm olein.…”
Section: A R T I C L E I N P R E S Smentioning
confidence: 96%
“…However, the preliminary investigation of these technologies that focuses too much on the early stage, neglected the more crucial stage; delivery and persistence of the BCA in the environment for a continued control (O'Brien, 2017). Once again in 2020, we see a surplus of publications identifying potential microbes, their modes of actions and disease suppression either in the laboratory or in the nursery stages (Ahmad et al, 2020a;Anggita et al, 2020;Goh et al, 2020a;Naeimi et al, 2020;Parvin et al, 2020;Pramudito et al, 2020). There were no article focusing into the efficacy of an established product in the field.…”
Section: A R T I C L E I N P R E S Smentioning
confidence: 99%
“…The oil is pre-treated using degumming and bleaching processes, followed by deacidification and deodorisation using molecular distillation (Van Rooyen et al, 2008). These milder processes allow the oil to retain beneficial phytonutrient compounds such as carotenes and antioxidants that are lost during physical and chemical palm oil refining processes (Loganathan et al, 2020). There are reports of the potential use of RPO and its derivatives in the development of fatbased food products such as margarine and shortening (Nagendran et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Tocotrienols are important in improving cognition, bone health, longevity, and cholesterol level in blood plasma, besides exhibiting neuro-and skin-protective effects (Meganathan and Fu, 2016;Cestaro et al, 2017). A number of studies reported the synergistic effect of carotenoids and vitamin E as super natural antioxidant in oils (Kamaruzaman et al, 2015;Loganathan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%